Cetaceans and conservation in the Canary islands - Martín, Vidal; Servidino, Antonella; Tejedor, Marisa; Arbelo Hernández, Manuel Antonio; Brederlau, Bernd; Neves, Silvana; Pérez Gil, Mónica; Urquiola, Erika; Pérez Gil, Enrique; Fernández Rodríguez, Antonio Jesús (2009)
Canary Islands (Spain), in the Lower North Atlantic, are a well-known hot spot for eetaeean diversity. Nevertheless, no official species list has been compi!ed up to date. For the proscnt analysis three sourees were used: I) 1.833 sightings recorded in different mu\tispecie.???? studies rea!ir.ed by SECAC between 1999 and 2009. 2) 2.100 opportnnistic sightings sinee 1995, 3) 850 specimcns stranded between 1980 y 2008 from SECAC and IUSA's databases. Thc stranding record ineludcd mass strandings of G. ,nacrorhynch11s, T. 1nmca1us aud S. /ongiros1ris, and a die-off episode of S. bredane11sis in 2007, und 1 1 atypieal mass stmndings of beaked whales. Currently, 28 cctacean &????ies have been recordcd iu this Archipelago. The most frequent speeics in the sight:ing record are G. macrorhynch11s, T. trunca tu., and S. Jrontali$. Toe most lrequent species in the stnmding recon! are S. coeroleoalba, D. delphis and S. frontali,,. Sightlng and stmnding data analysis show that: 1) T. troncatus, G. macrorhy11chus, S. coendeoalba, G. griseus, P. ,nacrocephalus, K. breviceps, Z. carirostris, M. densirossris and M. e11rop11e11s aro regu!afiy present year-ro11nd; 2) S. Jrontalis, S. bredaneMis. B. brydeiore seasoually present, with slight variations bet????cn years; 3) D. ddphis and B. physa/us show a strong seasonality; 4) L hasei and K. simn are instead rare species; 5) thrcc rccords of each specics eonfü:mcd the prcscncc of E. glacial is and B. musculus in the last 15 years; 6) P. plwcoena, M. bidens, G. melas and S. langirostris are extralimita] records. Toe presence of M. mirns is still doubtfu!. Conccm for conservation oí cetaecans in !he Canary lslands is relalcd to habitaL degradation duc to sinergie lhreaths for lo????al populations of bolllenose dolphins (e.g., small confliets with 1mditional fishery, maritime tmffic, whalc-wntching), antropogenie noise for beaked whales and collisions, especially with sperm whale.